Stable Soil Moisture Improves the Water Use Efficiency of Maize by Alleviating Short-Term Soil Water Stress - Niu, Li; Wang, Zhuan; Zhu, Guolong; Yu, Kefan; Li, Ge; Long, Huaiyu (Frontiers in Plant Science, 2022)
Weaker temporal variation of soil moisture can improve crop water use efficiency, but its physiological mechanism was still unclear. To explore the mechanism, an organized experiment was conducted in Beijing from June to September. From jointing stage to maturity stage of maize, stable soil moisture (SSM) and fluctuating soil moisture (FSM) was established with Pressure Potential Difference-Crop Initiate Drawing Water (PCI) and manual irrigation (MI) respectively to explore the physiological mechanism of SSM to improve maize water use efficiency. Among them, PCI treatments was set with 3 pressure differences of -5, -10 and -15 kPa, and MI treatment was watering every 3 days with the irrigation amount of 9.3 mm. The results showed that: (1) After water treatment, the average soil water content of PCI-5 kPa, PCI -10 kPa, PCI -15 kPa and MI treatments were 53% field capacity (FC), 47% FC, 38% FC and 78% FC, respectively. It was SSM with weak temporal variation under PCI treatments, and FSM with medium temporal variation under MI treatment. (2) PCI treatments reduced the content of proline, malondialdehyde and abscisic acid in each organ of maize. (3) Compared with FSM 78% FC, the maize root activity at filling stage of 53% FC SSM and 47% FC SSM increased significantly by 57.1% and 28.6%, respectively, and the carbon isotope discrimination value (Δ13C) in bracts of the two treatments increased by 18.3% and 10.4%, respectively. (4) There was a very significant positive correlation between water use efficiency based on biomass (WUEb) and Δ13C in bracts. In conclusion，a large temporal variation of soil moisture was an important factor that caused water stress in maize. Under stable soil moisture treatments, the accumulation of abscisic acid, proline and malondialdehyde was synergistically reduced. Stable soil moisture improved the water use efficiency of maize by alleviating short - term soil water stress caused by the fluctuation of soil moisture.